Ionic-Liquid-Infused Nanostructures as Repellent Surfaces - Galvan, Yaraset; Phillips, Katherine R.; Haumann, Marco; Wasserscheid, Peter; Zarraga, Ramon; Vogel, Nicolas (Langmuir, 2018)
In order to prepare lubricant-infused repellent coatings on silica nanostructures using low vapor pressure ionic liquids as lubricants, we study the wetting behavior of a set of imidazolium-based ionic liquids with different alkyl side chains as a function of the applied surface functionalities. We take advantage of the structural color of inverse opals prepared from a colloidal coassembly technique to study the infiltration of ionic liquids into these nanoporous structures. We find that the more hydrophobic ionic liquids with butyl and hexyl side chains can completely infiltrate inverse opals functionalized with mixed self-assembled monolayers composed of imidazole groups and aliphatic hydrocarbon chains, which we introduce via silane chemistry. These molecular species reflect the chemical nature of the ionic liquid, thereby increasing the affinity between the liquid and solid surface. The mixed surface chemistry provides sufficiently small contact angles with the ionic liquid to infiltrate the nanopores while maximizing the contact angle with water. As a result, the mixed monolayers enable the design of a stable ionic liquid/solid interface that is able to repel water as a test liquid. Our results underline the importance of matching chemical affinities to predict and control the wetting behavior in complex, multiphase systems
Keywords: Coating materials; Salts; Liquids; Wetting; Solvents